Behaviour of truck’s compressor’s connecting rods made of aluminium alloy under different manufacturing conditions - Kandrotaitė-Janutienė, Rasa (Transport, 2016)
The main objective of this study was to explore quality increasing and cost reduction opportunities for a production of forged aluminium alloy 6082 connecting rods. These automotive parts are used for air compressors’ of the trucks. Connecting rods undergoes high cyclic loads during exploitation, therefore, the durability of this component is of a critical importance. The main factors characterizing high durability of the connecting rod are hardness and impact strength that may be achieved selecting the proper technology regimes. The main requirements for the aluminium alloy 6082 are hardness in the range of 90–120 HB and impact strength not less than 29.2 J/cm2. Furthermore, the main problem is a stability of testing results of randomly picked connecting rods as these parts are produced in big quantities for the export purposes. Our experiments and recommendations for the development of technology of connecting rods’ allowed maintaining the requirement in hardness, increasing the impact strength approximately twice and reducing the time needed for the production of one connecting rod as it let to save the cost of the part. First published online: 15 Jun 2015